2009
DOI: 10.1103/physrevb.80.075411
|View full text |Cite
|
Sign up to set email alerts
|

Roles of defects induced by hydrogen and oxygen on the structural phase transition ofSi(111)4×1-In

Abstract: The influences of surface defects created by hydrogen and oxygen adsorption on the ͑4 ϫ 1͒ → ͑8 ϫ 2͒ structural phase transition in an In/Si͑111͒ system have been studied using low-energy electron diffraction. The transition temperature ͑T c ͒ decreased with the hydrogen exposure as compared to the clean surface, whereas it increased with the oxygen exposure. The H-induced decrease in the T c is expected and explainable by the general destructive role of defects as random disorders in the transition. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 46 publications
(39 reference statements)
1
26
1
Order By: Relevance
“…In this study, we restrict ourselves to the adsorption of oxygen, which chemisorbs dissociatively at room temperature on In/Si(111) [13], in agreement with theory [14]. Interestingly, oxygen increases T c , while many other adsorbates show the opposite behavior [15,16]. Moreover, it was shown that single oxygen defects also induce a structural phase transition in the adjacent defect-free In chain [17].…”
Section: Introductionmentioning
confidence: 74%
“…In this study, we restrict ourselves to the adsorption of oxygen, which chemisorbs dissociatively at room temperature on In/Si(111) [13], in agreement with theory [14]. Interestingly, oxygen increases T c , while many other adsorbates show the opposite behavior [15,16]. Moreover, it was shown that single oxygen defects also induce a structural phase transition in the adjacent defect-free In chain [17].…”
Section: Introductionmentioning
confidence: 74%
“…Global characteristics such as the transition temperature (T c ) and transport property of this In/Si(111)-4×1 surface have been reported to be affected significantly by small amounts of defects [13,[20][21][22][23][24][25][26][27][28]. In a recent series of diffraction experiments, the defects created by depositing metal atoms (In and Na) or by exposing the surface to gases (hydrogen and oxygen) were found to change the transition temperature [23][24][25]27].…”
Section: Introductionmentioning
confidence: 96%
“…In a recent series of diffraction experiments, the defects created by depositing metal atoms (In and Na) or by exposing the surface to gases (hydrogen and oxygen) were found to change the transition temperature [23][24][25]27]. Of particular interest was the adsorption of oxygen, which increased the T c of the phase transition of the In/Si(111)-4×1 surface, whereas the other defects reduced it.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In case of Si(111)-In, e.g., the critical temperature T C for the metal insulator transition can be shifted to lower temperatures by adsorption of various atoms, which commonly destabilize the low-temperature phase. On the contrary, molecular oxygen atoms enhance cooperatively the interwire and intrawire coupling and lead to a stabilization of the insulating (8 × 2) configuration, which * tegenkamp@fkp.uni-hannover.de increases T C [12][13][14][15]. Moreover, on the Si(111)-Au (5 × 2) Si adatoms are intrinsically present and even mandatory for the formation of the geometry with the lowest (free) energy [16,17].…”
Section: Introductionmentioning
confidence: 99%